An Error Analysis in the Use of Simple Past Tense on Students’ Final Work at IAIN Kudus - Setyaningrum, Anisah (Institut Agama Islam Negeri Kudus, 2018)
This research aims at identifying, classifying and analyzing the kinds of errors on the use of simple past tense in students’ final work. It is expected to help the lecturers in identifying the students’ most common error in language learning processes, especially in learning simple past tense. Several stages are done in this qualitative research, they are: preparation, data collection, and analyzing the data. As the preparation, the writer try to read some theories and previous studies related to this research. In analyzing the data, Ellis’ theory is used in this research. The techniques in analyzing the data are: identification of error, classification, description, and correction. The result of this research shows that there are four kinds of errors made by students, they are omission 13%, addition 5%,misinformation 31%,and misordering 5%. They mostly make errors in the misinformation of irregular past verb in using The Simple Past Tense.